X2-z-6=0

Simple and best practice solution for X2-z-6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2-z-6=0 equation:



X2-X-6=0
We add all the numbers together, and all the variables
X^2-1X-6=0
a = 1; b = -1; c = -6;
Δ = b2-4ac
Δ = -12-4·1·(-6)
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-5}{2*1}=\frac{-4}{2} =-2 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+5}{2*1}=\frac{6}{2} =3 $

See similar equations:

| X2-21x-20=0 | | 3t-1=-22 | | 7x+9+22=180 | | 17-3x=x+5 | | 2/3x+1/2=5/6= | | 5x+1.75x=12x+1.25x | | -14=-7m-7m | | H2+8h–84=0 | | 207-v=90 | | x2-95=14x | | −7x+4=−10x−14 | | 20=1f+14 | | -7x+4=−7x+4=−10x−14 | | −24x−15=−27x+12 | | 5=2d-11 | | 6h+5=14 | | 5x+1.75=12x+1.25 | | 4(x-10)-12x=32 | | -7(x+3)-10x=30 | | 33=8s-15 | | 35-2k=17 | | 6=|8x+3| | | -2(3x-5)+10x=54 | | 5x+1.75=12+1.25 | | 1+7x-6=-12 | | 5(6x-3)=3(1+x) | | 4x-18=-18+3x | | 180+45x=-170 | | -7a=2 | | 19=3g-5 | | -2=a/8 | | 215=-w+120 |

Equations solver categories